Impact of Globalization on Consumer Food Behaviour: A Comprehensive Review - Swapnil Singh; Preeti Singh; Ajay Kumar Baheliya; Anjali Srivastava; Archna Yadav (Archives of Current Research International, 2024)
The current market dynamics, including consumer food behaviour, are profoundly influenced by the processes of civilizational and cultural evolution, as well as the ongoing globalization phenomena. The discourse begins with an exploration of the theoretical underpinnings of globalization and its intersection with consumer food behaviour. It further delves into the broader phenomenon of globalization in the contemporary era and elucidates its specific impacts on the dietary and purchasing habits of consumers. The reviewed studies indicate that globalization has significantly influenced various aspects of consumer food behaviour. These include changes in grocery shopping patterns, an increased frequency of fast food consumption, and a heightened interest in both comfort foods and novel dining experiences. The pervasive reach of global media, multinational food corporations, and international supply chains has facilitated the widespread availability and popularity of diverse food products and dining practices across different cultures and regions. However, globalization’s impact is not unidirectional. It has also catalysed the emergence of counter-movements and alternative consumer attitudes. There is a growing preference for locally sourced and environmentally sustainable food products, reflecting a backlash against the perceived homogenizing effects of globalization. Movements such as the Slow Food movement advocate for traditional and regional cuisine as a means of preserving cultural heritage and promoting sustainable agricultural practices. Additionally, heightened awareness of food safety and quality has led to an increased demand for organic and non-genetically modified food products.